On single-station, six degree-of-freedom observations of local to regional seismicity at the Piñon Flat Observatory in Southern California - Andreas Brotzer; Heiner Igel; Felix Bernauer; Joachim Wassermann; Robert Mellors; Frank Vernon (Seismica)
In September 2022, a portable, three-component rotational rate sensor, namely a blueSeis-3A gyroscope, has been deployed at the underground vault of the Pinon Flat Observatory (PFO) in southern California. A three-component, broadband seismometer is co-located, jointly forming a six degree-of-freedom (DoF) station for long-term observations of local and regional seismicity and multi-component wavefield studies. The seismic recordings are available online via IRIS FDSN services as PY.BSPF (BlueSeis at Pinon Flat).  The instrumentation at PFO additionally provides high-quality strain observations, allowing now to study translation, rotations and strain of the seismic wavefield in a low noise and high seismicity area (e.g. San Andreas fault zone). The seismic array at PFO is used to compute array derived rotations and validate the direct observations of rotational ground motions. We show results of 6-DoF processing applied to a local Mw 4.1 and a regional Mw 6.2 event to obtain backazimuth estimates, which we validate with array beamforming, and estimates of local seismic phase velocities. For observed events between October 2022 and October 2023, we detect more than 400 events of which 118 are triggered on all six components. Peak rotation rate amplitudes are used to derive empirical peak amplitude relations for vertical and horizontal rotation rates to provide valuable insights towards resolvability for comparable 6~DoF campaigns. We find the dominating limitations for rotational motion observations currently to be set by the self-noise level of the blueSeis-3A rotation sensor and encourage further instrumental development.